International Survey Regarding the Use of Rehabilitation Modalities in Horses - Wilson, Janine M.; McKenzie, Erica; Duesterdieck-Zellmer, Katja (Frontiers in Veterinary Science, 2018)
A survey querying the use of 38 different rehabilitation therapies in horses was distributed to eight national and international veterinary groups with the objective of defining which modalities are most commonly utilized in horses, and the specifics of their application. A total of 305 complete or partial responses were obtained from over 10 geographic regions; 75.4% from private equine practice or regional private equine referral hospitals, 14.1% from university teaching hospitals or satellite clinics, 8.2% from private mixed animal practice, and 2.3% from veterinary rehabilitation centers. The majority of respondents were located in the USA (60%), Europe (25.6%) and Canada (5.6%). Respondents reported working with athletic horses primarily in the disciplines of hunter-jumper (26.9%), dressage (16.0 %), and pleasure riding (14.7%), followed by Western riding, track racing and eventing. Warmbloods (39.7%) were the predominant breed presenting to respondents, followed by Thoroughbreds (20.3%) and Quarter Horses (17.3%) ahead of other breeds. All 38 modalities were used by respondents. The ten most prominently utilized were controlled hand walking (97.3%), therapeutic shoeing (96.1%), ice (95.2%), compression bandaging (89.5%), platelet rich plasma (PRP; 86.5%), therapeutic exercises (84.3%), interleukin-1 receptor antagonist protein therapy (IRAP; 81.4%), stretching (83.3%), and cold water hydrotherapy (82.9%). Heat (77.6%), massage (69.0%) and acupuncture (68.3%) were also commonly utilized. The least prominently used modalities were hyperbaric oxygen therapy (9.4%), cytowave (8.3%), and radiofrequency (6.4%). Injectable therapies (IRAP, PRP, mesotherapy, stem cells) were almost solely administered by veterinarians; other modalities were variably applied by veterinarians, technicians, veterinary assistants, farriers, physical therapists, trainers and other entities. A total of 33% of respondents reported working collaboratively with physical therapists on equine patients. Findings indicate that a broad range of invasive and non-invasive modalities are used in equine patients to address a variety of rehabilitation and performance needs, and that personnel with varying levels of expertise are involved in their administration. This suggests that further investigation to better define the delivery, efficacy and any negative effects of many of these modalities is important.